Youth and Media Consumption in the Covid-19 Era in Mauritius - Chenganna, Azhagan (Journal of Communications, Media & Society, 2022)
News diffused across media platforms increasingly form part of youth media consumption. The attention of the youth is continually solicited online and incidental news is constitutive of their everyday practice. In a notable way, Covid-19 and its restrictions have induced the youth to organize their lives digitally in an environment of news abundance. Beyond rational usage which often molds understanding of news and media consumption, this paper asks ‘can an ‘affective turn’ provide insight into youth incidental news media consumption during the Covid-19 pandemic?’ Through the notion of liminality, the paper questions incidental news and media consumption by the youth and the extent to which these are tied to their lived experiences. It delves into the habits of media consumption generally, with a focus on incidental news consumption in the participatory cultures of social media and considers the need to grasp youth media use and consumption as a social experience that is liminal. Through interviews with final year Mauritian secondary school students, this paper argues that the experiences of incidental news and media consumption encompass experiences which are affectively loaded and which evolve around passive and active engagements. It emphasizes the role of the platforms as gateways and gatekeepers. Through a decolonial lens, it makes the case for dialogic perspectives to offset the challenges posed by the platforms.
Research Article
Keywords: Youth, Media Consumption, Covid-19, Mauritius